Coal consumption and economic growth in Indonesia: An analysis of restricted structural var - Haris Annannab; Aminu Zubairu Surajo; Farabi Ahmad (Economics, Business, Accounting & Society Review, 2022)
The aim of this paper is to investigate the effect of coal consumption, economic growth, and population to the greenhouse gas emission in the case of Indonesia. The foundation of this study is the reality that Indonesia's economic growth is spur by population growth which requires the consumption of electricity in the large amounts produced using coal as the main fuel. The consumption of coal as the main fuel causing fatal environmental damage. Theoretically, the higher the population and economic growth, the greater the environmental damage that will occur. The data used in the study are during the period of 1971 – 2018 with VAR restricted model and structural VAR as the methodology employed. The result of the analysis shows that the increase of coal consumption, population, and population in Indonesia effects positively to the increase of greenhouse gas emission where population contributes the biggest effect. In addition, the results also confirmed that the growth of population can spur the demand of coal consumption and economic growth which later increase the greenhouse gas emission. Population in Indonesia become the most contributor in affecting the fluctuation of greenhouse gas emission. The study recommends to the policy makers to start produce the electricity based on the renewable energies resources and reduce the consumption of fossil energy especially coal as the fuel of power plants. It is because, the biggest consumption of coal is used by the power plants to produce the electricity